Partial Inner Product Spaces: Some Categorical Aspects - Jean-Pierre Antoine; Dominique Lambert; Camillo Trapani (Advances in Mathematical Physics)
We make explicit in terms of categories a number of statements from the theory of partial inner product spaces (PIP-spaces) and operators on them. In particular, we construct sheaves and cosheaves of operators on certain PIP-spaces of practical interest.